Experiencing nature : the Spanish American empire and the early scientific revolution - Barrera-Osorio, Antonio, 1964- (University of Texas Press, 2006)
"In this book, Antonio Barrera-Osorio investigates how Spain's need for accurate information about its American colonies gave rise to empirical scientific practices and their institutionalization, which, he asserts, was Spain's chief contribution to the early scientific revolution